Losing an enemy : Obama, Iran, and the triumph of diplomacy - Parsi, Trita (Yale University Press, 2017)
The definitive book on Obama's historic nuclear deal with Iran from the author of the Foreign Affairs Best Book on the Middle East in 2012This timely book focuses on President Obama's deeply considered strategy toward Iran's nuclear program and reveals how the historic agreement of 2015 broke the persistent stalemate in negotiations that had blocked earlier efforts. The deal accomplished two major feats in one stroke: it averted the threat of war with Iran and prevented the possibility of an Iranian nuclear bomb. Trita Parsi, a Middle East foreign policy expert who advised the Obama White Hous.